Human physiology : - Vander, Arthur J. (WCB McGraw-Hill, 1998)
Vander’s Human Physiology, eleventh edition, carries on the tradition of clarity and accuracy, while refining and updating the content to meet the needs of today’s instructors and students. The eleventh edition features a streamlined, clinically oriented focus to the study of human body systems. It has also responded to reviewer requests for more clinical applications. Chapter 19 is new and contains three complete case studies. Physiology Inquiries have also been added to many figures throughout the chapters. These critical-thinking questions are just one more opportunity to add to the student’s learning experience.